The Electronic Registration of Liability Rights - Arief Rahman; Wiwiek Wahyuningsih; Sinta Andriyani (Faculty of Law, University of Mataram, 2021)
This research aims to examine the inhibiting factor of electronic mortgage registration procedures. The type of this research is empirical normative legal research by using the statutory, conceptual and empirical approach. The result shows that the electronic registration of mortgage performed through several steps, namely: (1) login to the application of electronic land services; (2) choosing the mortgage service on the menu bar; (3) submit an application to make a mortgage file; (4) completing the entry; (5) uploading the necessary documents; (6) confirming file; (7) paying a deposit order for the security rights registration; (8) recording and issuance of mortgage certificate. While the inhibiting factors on the electronic registration of mortgages are: (a) there is some official land registrar (in short term known as PPAT) who do not understand the registration procedures of electronic mortgage rights services. (b) the PPAT has not validated and registered their data in the PPAT Partner application at mitra.atrbpn.go.id; (c) the creditors have not validated and registers in the financial services partners application at mitra.atrbpn.go.id (d) the certificate of land rights has not been validated which will be used as the object to grant a mortgage right. Before the deed of mortgage rights granted, at the time of the checking the PNBP can only be paid a day after the validation completed; (e) the server problem which often occurred when uploading the requirements and the deed documents; (f) the required documents for filing a mortgage rights application are not complete.